The effects of job satisfaction, organizational justice and career development towards employee's turnover intention: an analysis among industrial and manufacturing workers in Kota Kinabalu, Sabah. - Mohamad Aizat Zulkafli (2014)
This study has been carried out to understand the relationship between job satisfaction, perceived organizational justice, career development and perceived organizational commitment towards turnover intention of the employees in manufacturing sectors located in Kota Kinabalu areas. This study seeks to contribute to the development of a conceptual framework that integrates the variables. This study was conducted based on non-probability sampling in Sabah, Malaysia with focus point in the area of Kota Kinabalu. The research sample was selected from a range of employees who working in selected in private sector based on convenience sampling. The method of data collection is self-administered questionnaire. Quantitative data obtained and the data gathered were being treated by using the statistical program namely Statistical Package for Social Science ( SPSS) version 22.0 and SMARTPLS for analysis and summarization purpose. Prior to the study, a comprehensive literature review was performed. The literature review informed the theoretical which guide the study. Additional literature, where needed was introduced through data collection and analysis processes. The study uncovered that job satisfaction, perceived organizational justice, career development and perceived organizational commitment towards turnover intention among the respondents